The association of dietary components with depression and anxiety symptoms: findings from a cross-sectional survey - Gillespie, Kerri M.; Kemps, Eva; White, Melanie J.; Bartlett, Selena E. (Frontiers in Nutrition, 2025)
IntroductionIt is understood that diet has a significant impact on health. However, the associations between individual macronutrients and mental health are poorly understood. We aimed to investigate the relationship between dietary components and symptoms of depression and anxiety.MethodsA cross-sectional study of 129 healthy adults was conducted using an online food frequency questionnaire and measures of depression, anxiety, and early life experiences.ResultsOf the sample, 31% experienced moderate or severe anxiety and/or depression. Sugar-sweetened beverage (SSB) intake was positively associated with depression (β = 4.827; 95% CI: 0.954, 8.7; p = 0.015). Dietary fibre was negatively associated with anxiety (β = -2.306; 95% CI: -3.791, -0.82; p = 0.003). Moderate caffeine consumption (100-300mg) was associated with reduced depression (β = -4.099; 95% CI: -7.049, -1.15; p = 0.007). Women experienced higher rates of depression and anxiety. We found evidence suggesting an association between high-fructose corn syrup and depressive symptoms and a potential protective effect of fibre on anxiety. A U-shaped curve for caffeine may be present, with moderate consumption associated with improved mental health.DiscussionA significant positive association was found between SSB consumption and depression, while a negative association was found between fibre consumption and anxiety. Additional prospective studies with repeated dietary data capture are needed to affirm these findings.